Differences in motivation and dropout among athletes from different individual and team sports - Nekic, J.; Mavra, N.; Penezic, Z. (World Congress of Performance Analysis of Sport XII, 2018)
Objectives: The purpose of this study was to evaluate the psychometric properties of scores derived from the PMQ and the drop-out scale. This study compared athletes' motivational characteristics in individual and team sports. It explored significant individual, social and environmental factors and how they interact to influence participation in sport for adolescent. In total. 203 athletes completed PMQ and Dropout scale. 114 from individual and 89 from team sport (3 individual and 3 team sports). Methods: 203 participants, competitive athletes, aged 14-19. were invited to participate in this study. There were 131 males and 72 female athletes from 6 different sports: 56.2% were from individual sports (swimming, athletics, tennis) and 43.8% athletes came from team sports (volleyball, basketball, water polo). The questionnaire used in this investigation to assess participants` motivation was Participation Motivation Questionnaire, designed by Gill. Gross & Huddleston. 1983. It assesses 30 questions focusing on skill/competence, status/acknowledgment energy release, team atmosphere and affiliations. The follow -up questionnaire was Dropout questionnaire designed for the purposes of this research with aim to get more information on the different reasons for leaving sport. Results: The results show that there are significant differences in motivation participation depending on the sport. There are differences between swimming and - basketball, water polo and athletic. Basketball players are attained the most, while the results show that least motivated athletes are swimmers. The result revealed that type of school (elementary school or high school) doesn`t make a difference in motivation or in withdrawal aspects. According to the reasons named in dropout questionnaire there are no differences between individuals who are engaged in different sports. There are differences in dropout questionnaire where sources within the individual are gender-dependent. Girls have more prominent reasons to leave the sport than boys do. There is no school influence ie. athletes do not differ depending on whether they attend elementary or high school. Based on number of sessions per week, analysis showed that group 1 (more than 8 sessions per week) is most persistent in training and shows less dropout, compared to groups which have less sessions per week. Conclusions: The results of this study support the importance of negative factors related to the aspects of the athletic environment that lead to discontinuing in competitive sport. Our investigation confirms that research in sport withdrawal (dropout factors) must neglect type of the sport (individual or team sport) because there were no significant results found on this topic.